Histopatologi Organ dan Hematologi Ikan Lele Hasil Perbenihan di Airnona, Kota Kupang, Nusa Tenggara Timur - Juanda, Shobikhuliatul Jannah; Lukmini, Aisyah; Rahman, Ihsan Sanggar; Putri, Rizka Rahmana (Journal Galung Tropika, 2023)
This research aims to determine damage to gill and liver tissue through histopathological analysis and the hematological picture of catfish seeds produced by farmers in Airnona, Kupang City, East Nusa Tenggara. A total of 100 fish seeds were taken randomly from the hatchery pond. Hematological observations are carried out by making blood smears, while histopathological observations are carried out by making histology preparations. Hematological and histopathological observations were carried out using a microscope at 140-800X magnification. The histopathological analysis of the gills showed damage, including mucus cell proliferation, epithelial lifting, edema, necrosis, vacuoles, and parasitic investment. The liver shows damage in vacuoles, hemosiderin, congestion, the presence of Melano Macrophage Center (MMC), sinuses, fatty degeneration, and hemorrhage. Abnormalities in blood cells observed in blood smears of fish seeds include spherocytes, lacerated membranes, blebbed nuclei, lysis, and necrosis.